Analisis Pengaruh Kepuasan Dan Loyalitas KonsumenTerhadap Pembelian Abon Sapi Gloria(Studi Kasus Pada Masyarakat Boyolali) - Wijanarko, Koko; , Basworo Dibyo, S.E, M.Si (2016)
The purpose of this study were: 1) to analyze the influence of consumer satisfaction of consumers to purchase abon GLORIA; 2) to analyze the influence of consumer loyalty of consumers to purchase abon GLORIA; 3) Analyze the effects of customer satisfaction and customer loyalty to purchase abon GLORIA; and 4) to analyze the independent variables consisting of customer satisfaction and loyalty, the most influence on the purchase abon GLORIA in the town of Boyolali. This research is a survey. The study population is all consumers abon GLORIA, a sample of 100 people by using purposive sampling, sampling with certain criteria, namely the consumers who are domiciled in Boyolali. Data analysis methods: 1) test the research instrument, namely the validity and reliability, 2) test the classic assumption, namely normality test, multicollinearity, heteroscedasticity, autocorrelation, 3) Ujimultiple linear regression, 4) Test Godness of Fit, that the t test, F test and the coefficient of determination (R2). The results showed: 1) Customer satisfaction significant positive effect on consumer purchasing decisions, meaning that the higher level of customer satisfaction, the higher the subsequent purchasing decisions, and conversely the lower the level of customer satisfaction, the lower the purchasing decision back. 2) Consumer loyalty significant positive effect on repurchase decisions, meaning that the higher level of consumer loyalty, the higher the subsequent purchasing decisions, and conversely the lower the level of consumer loyalty, the lower the purchasing decision back. 3) satisfaction and customer loyalty significantly influence the purchasing decision back, meaning jointly satisfaction and loyalty significantly influence the purchasing decision back. Keywords: Satisfaction, Loyalty, Purchasing Decisions.